APLIKASI LOCATION BASED SERVICE FASILITAS UMUM BERBASIS ANDROID - Mudzakir, Amat; Arifudin, Riza (Universitas Negeri Semarang, 2015)
The purpose of writing this article is to make LBS application design and implement public facilities . The method used for the development of this application is to use the model prototypes consisting of phase identification, analysis phase, design phase, and the phase of the trial . Public facilities LBS applications are created using the Android Development Kit, XAMPP, Adobe Dreamweaver CS 6, and Eclipse IDE for Java as frameworknya while The programming language used is Java, XML, and PHP . The data used is data information on public facilities . Final results reveal that the application can be implemented well in the manifold android mobile phones and tablets that have a version of Gingerbread 2.3 to 4.3 Jelly Bean with a screen size of no more than 5 inches .